Report on the Development and Expansion of MRV in the Philippines - International Rice Research Institute (International Rice Research Institute, 2025)
Despite being a top global producer, the Philippine rice sector struggles with stagnant productivity due to climate risks, structural inefficiencies, and a heavy reliance on imports. As the primary source of agricultural greenhouse gas emissions, the sector is central to the nation’s 75% emission reduction goal, primarily through climate-smart practices like Alternate Wetting and Drying (AWD). To unlock carbon finance and track progress, the country is leveraging data systems like PRiSM and RiceLytics, though it still faces gaps in stakeholder coordination and formal verification processes. Current initiatives, such as the AcceLER project, aim to bridge these gaps by scaling digital Monitoring, Reporting, and Verification (MRV) systems to help the Philippines meet its climate commitments.